The Liriomyza (Diptera: Schizophora: Agromyzidae) of Canada & Alaska - Lonsdale, Owen (Zootaxa, 2017)
The Liriomyza (Diptera: Agromyzidae) of Canada and Alaska is revised, with species keyed and illustrated, and new host and geographic records provided. Eighty one species are recognized, including 24 new to science: L. agrios, L. albispina, L. anatolis, L. aphila, L. apilaca, L. aquapolis, L. arenarium, L. atrassimilis, L. bicolumbis, L. charada, L. cracentis, L. elevaster, L. emaciata, L. fumeola, L. gibsoni, L. griffithsi, L. hilairensis, L. limopsis, L. mesocanadensis, L. pilicornis, L. pistilla, L. rigaudensis, L. taraxanox, L. taraxanuda, L. tryssos. Ten species known from the United States are recorded as new to Canada: L. artemisiae Spencer, L. assimilis (Malloch), L. baccharidis Spencer, L. helianthi Spencer, L. merga Lonsdale, L. minor Spencer, L. sabaziae Spencer, L. temperata Spencer, L. violivora (Spencer) and L. virgo (Zetterstedt). Palaearctic species new to North America include L. wachtli Hendel and L. flaveola (Fallén); while the latter species has been recorded in North America before, all previous records represent misidentifications. Hosts are recorded for the first time for L. balcanicoides Sehgal, L. minor Spencer, L. orilliensis Spencer and L. socialis Spencer. Galiomyza Spencer syn. nov. is included as a junior synonym of Liriomyza Mik, resulting in six new combinations.